The Effect of Animated Videos on the Prevention of Sexual Behavior on Knowledge And Attitudes in Junior High School Students - Santi, Septiana Rahma; Widjanarko, Bagoes; Musthofa, Syamsulhuda Budi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Premarital sexual activity in adolescents in recent decades has increased globally. lack of understanding adolescents can be at risk of having unhealthy dating behavior, can even encourage adolescents to engage in sexual behavior to premarital sex which has an impact on teenage pregnancy and sexually transmitted infections. Prevention efforts that can be done are health education involving attractive media such as educational videos using animation as a very suitable alternative option in order to influence understanding and change the behavior of individual groups. Objective: The purpose of this study was to determine the effect of animated videos on the prevention of sexual behavior on the knowledge and attitudes of junior high school students. Methods: This study is a quantitative study with a quasi-experimental design using a pretest-posttest with control group design, which was conducted on students aged 13-15 years with 30 respondents as an intervention group, and 30 respondents as a control group. Results: Statistical analysis test in the intervention group using the Wilcoxon test found that there was an increase in knowledge and attitudes after being given an animated video with a p-value of 0.000. Statistical tests using Mann Whitney and Independent T-Test found that there were differences in the level of knowledge and attitudes between the intervention group after treatment and the control group with a p-value of 0.000. Conclusion: There is a difference in the level of knowledge and attitude of students before and after being given animated videos and leaflets in the intervention group. There is a difference in the level of knowledge and attitude of students in the intervention group who were given treatment in the form of animated videos with the control group who were not given treatment and only given leaflets.